Erratum: Hubungan Kecerdasan Emosional dan Self-Efficacy Dengan Penguasaan Teknik Roll Kayak Slalom - Ramdhani Rahman; Nurlan Kusmaedi; Komarudin Komarudin (JUARA : Jurnal Olahraga, 2020)
Correction to: JUARA: Jurnal Olahraga This corrects the article DOI: https://doi.org/10.33222/juara.v4i2.628 This article was originally published using English metadata in the article title and this is our fault. but now the article metadata has been changed in Indonesian and appears correctly in the current article.